Measuring the Potential of Locality of Sufism as a Mechanical Greening Movement in Islam in East Java - Ahmad Imron Rozuli; Moh Anas Kholish; Abd. Rahman Ambo’ Dalle (Faculty of Social Science, Universitas Negeri Malang, 2022)
This article aims to examine the potential of the locality of Sufism as a mechanical green movement in Islam in Bojonegoro and Tuban. The research method used in the study of this article is a qualitative descriptive research method, with data collection techniques of in-depth interviews, observation, participants, and documentation. The results of the study of this article show that the role of the Rowobayan and Lintas Ghoib congregations as local communities with their mechanical awareness has considerable potential in encouraging grassroots community greening movements in Bojonegoro and Tuban. The two tarekats have a distinctive perspective in establishing the relationship between God, humans, and nature. The two congregations carried out the greening campaign, and the grassroots community was carried out mechanically by the murshid to their students. The existence of a murshid is the inheritor of the role of the Prophet Muhammad, who God appointed as a universal compassionate agent for the universe, which must be practiced in a transformative greening movement. In addition, the potential of the locality of Sufism as the basis for the greening action is its perspective which does not see the relationship between humans and nature as an exploitative subject-object relationship, like modern humans. These two local congregations try to establish a harmonious relationship between humans and nature with a mutualistic symbiotic relationship between subject and subject, not an exploitative subject-object relationship. These potentials were then practicalized mechanically by his students for river conservation in Bojonegoro and forest conservation in Tuban.